Hepatic focal nodular hyperplasia with congenital portosystemic shunt. Issue 6 (18th December 2014) - Cho, Yuki; Shimono, Taro; Morikawa, Hiroyasu; Shintaku, Haruo; Tokuhara, Daisuke
Abstract: Hepatic focal nodular hyperplasia (FNH) is a rare benign tumor in children. Vascular anomalies have been identified as pathological features of FNH, but the etiology remains unclear. We describe a rare case including the time course of formation of hepatic FNH in response to congenital portosystemic shunt (PSS). A 4‐month‐old girl was identified on newborn mass screening to have hypergalactosemia, but no inherited deficiencies in galactose‐metabolizing enzymes were found. Ultrasonography and per‐rectal portal scintigraphy showed intrahepatic PSS of the right lobe as a cause of the hypergalactosemia. At age 12 months, the patient had elevated hepatic enzymes and small hypoechoic hepatic lesions around the shunt. On abdominal contrast‐enhanced ultrasonography spoke‐wheel sign and central stellate scar were seen, which are typical features of hepatic FNH without biopsy. Congenital intrahepatic PSS should be evaluated on abdominal contrast‐enhanced ultrasonography and observed over time because of its potential to develop into hepatic FNH.